AB1170 First results of the rheumatoid arthritis handscan registry leeuwarden. (12th June 2018) - Al Hasan, A.; Bos, R.; Veeger, N.; Zhang, D.; Hendriks, L.; Wink, F.; Schilder, A.; Reimann, F.; Bergsma, K.
Abstract : Background: The handscan is a new technologic device which uses diffuse optical transmission in combination with blood flow modulation. It is a non-invasive measurement of joint inflammation potentially more sensitive than the clinical evaluation of the joints by a rheumatologist[. 1 However, more clinical data is necessary before this new device can be implemented in the daily clinical practice. Objectives: This study investigates the additional value of the handscan in decision making in the daily practice for patients with rheumatoid arthritis. Methods: At our outpatient clinic we started a registry for rheumatoid arthritis patients with a disease duration of at least two years. During this period, a handscan will be made for all patients before every regular visit. Both the patient and the treating rheumatologist will be blinded to the handscan outcome. Primary outcome is the association between DAS28 score and the total optical score (TOS) of the handscan per visit. Results: The study started in December 2017, until now 100 patients are included. The mean age was 61.1 years, the mean disease duration at time of inclusion 11.2 years, 67% were rheumatoid factor positive, 51% were anti-CCP positive. In figure 1 we show the association between DAS28 and the TOS in a linear model. Currently there is no validated cut off point for the TOS (negative or positive score for inflammation). In our group of 100 patients the median TOS was 10, the most discriminating TOS was found to be 17 using chi-square test as depicted in table 1. Conclusions: In this preliminary evaluation of the first 100 patients, we observed a limited positive correlation between the total optical score of the handscan and the DAS28. The TOS above 17 associates with moderate to severe disease activity. The definite clinical value of the handscan needs to be determined with longitudinal measurements and it's predictive value versus the DAS28. The ongoing current registry aims to answer these questions. Reference: [1] Van Onna M, Ten Cate DF, Tsoi KL, et al. Assessment of disease activity in patients with rheumatoid arthritis using optical spectral transmission measurements, a non-invasive imaging technique. Ann Rheum Dis2016;75:511–8. doi:10.1136/annrheumdis-2015-207315 Disclosure of Interest: A. Al Hasan Grant/research support from: this reserach is supported by an unrestricted grant from Stichting De Friesland, R. Bos Grant/research support from: this reserach is supported by an unrestricted grant from Stichting De Friesland, N. Veeger: None declared, D. Zhang: None declared, L. Hendriks: None declared, F. Wink: None declared, A. Schilder: None declared, F. Reimann: None declared, K. Bergsma: None declared